Rhetorical Anthropology or Anthropological Rhetoric: Foundations of the “Rhetoric & Anthropology” Research Net - Agnetta, Marco; Cattani, Adelino; Gil, Alberto; Jiménez Cataño, Rafael; Tapia Velasco, Sergio (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article is a scientific manifesto by the “Rhetoric & Anthropology Research Net”. It discusses the state of the subject, the basic principles of the investigation and an outline of different rhetorical-anthropological fields of work directed by the authors of the article. The methodological focus is ecological because it is based on responsibility and solidarity specified in a culture of debate worthy of the name, and in the principle of affirmation, that is, in a rhetoric that opens new pathways, provides solutions, and brings people together because it has an eminently positive orientation.
Keywords: rhetoric; anthropology; persuasion; responsibility; ethics; virtues